2011
DOI: 10.1152/ajpendo.00702.2010
|View full text |Cite
|
Sign up to set email alerts
|

Uterine signaling at the emergence of the embryo from obligate diapause

Abstract: Embryonic diapause is the reversible arrest of embryo development prior to implantation under a regime of uterine control that is not well understood. Our objective was to explore uterine modifications associated with the emergence of embryonic diapause in the mink, a species in which embryonic diapause characterizes every gestation. We investigated the uterine transcriptome at reactivation using the suppressive subtractive hybridization technique. A library of 123 differentially expressed genes between uteri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Although it has been reported that Hmgn1 was expressed in the uterus, 17 the detailed expression patterns of Hmgn1 in mouse uterus during early pregnancy have not been described. We thus performed in situ hybridization to localize the distribution of Hmgn1 mRNA in mouse uterus.…”
Section: Hmgn1 Mrna Expression During Early Pregnancymentioning
confidence: 99%
“…Although it has been reported that Hmgn1 was expressed in the uterus, 17 the detailed expression patterns of Hmgn1 in mouse uterus during early pregnancy have not been described. We thus performed in situ hybridization to localize the distribution of Hmgn1 mRNA in mouse uterus.…”
Section: Hmgn1 Mrna Expression During Early Pregnancymentioning
confidence: 99%
“…Blockade of Odc1 conversion of ornithine to the polyamine putrescine by the suicide inhibitor difluoromethyl ornithine (DFMO) prevents implantation in the mouse (Zhao et al, 2008) and reversibly arrests development in mink (Lefevre et al, 2011b) and mouse (Zwierzchowski et al, 1986) embryos. Expression of ODC1, along with the polyamine availability genes (Lefevre et al, 2011a) and uterine content of the polyamine putrescine (Lefevre et al, 2011b), are upregulated at the termination of diapause in the mink (Murphy, 2012).…”
Section: The Uterus Dictates Diapausementioning
confidence: 99%
“…For example, Arg can be converted to ornithine by arginase and ornithine converted to putrescine, a polyamine, by ODC1 [16]. Polyamines stimulate proliferation and migration of trophectoderm cells and are required for the transition of mink blastocysts in delayed implantation to an activated state for expansion and implantation [17,18]. Arg can also be metabolized by NOS to NO that stimulates proliferation …”
mentioning
confidence: 99%